Social Housing for Workers in Industrial Zones in Vietnam - Concepts and Practical Solutions towards Sustainable Development. The Case Studies of Hanoi City - Hoa, Ta Quynh Hoa; Dinh Tuyen, Pham (International Journal of Sustainable Construction Engineering and Technology, 2021)
Economic growth associated with the rapid industrialization and urbanization over the past 30 years since Doi Moi (Reform) has facilitated the establishment and development of many industrial zones (IZs) in major cities of Vietnam. The high concentration of IZs in the largest cities has attracted millions of industrial laborers and created large migration waves from rural to urban areas. Establishing and improving the living environment of workers have become a huge pressure for the Government and local authorities across the country to deal with. Although the Government has issued numerous policies and incentives to encourage and support housing development for factory workers, there are still many conflicts and challenges in policy implementation. Through observational and questionnaire surveys supported with in-depth interviews of experts in urban planning and management, the research aims to understand clearly the context of social housing development for IZ workers in Vietnam recently, to demonstrate outstanding characters of different types of housing for factory workers as well as crucial issues related to social housing and informal housing for factory workers. Furthermore, the research proposes solutions including legal institutions, management mechanisms, industrial worker housing database establishment, and basic technical solutions (planning and spatial organization) in order to find out some appropriate concepts for social housing targeted at industrial workers and then to achieve social sustainable development.